PENGARUH PROMOSI , KEPERCAYAAN TERHADAP MINAT BELI PRODUK TOUR PADA PT. GREEN DELI HOLIDAYS MEDAN - FAUZI . (JURNAL ILMIAH MAKSITEK, 2020)
This study aim to analyze the influenze of Promosiand Trust on Consumer Buy Interest of PT Green Deli Holidays Medan. Research variable include : Consumer Buy Interest (Y) as the dependent variable, Promosi (X1) as the independent variable, and (X2) as the independent variable. This study adopted the Marketing Management theory, as it pertaining to the Brand, Trust, and Consumer Buy Interest.This research applies a survey approach with a descriptive and qualitative method and uses an explanation power as it characteristics. The method of collecting the data is done by using interview, questionaires, and documentation study. The method of data analysis used is the multiple regression analysis and the simple regression analysis. The population of this study are 90 consumers of PT Green Deli Holidays Medan and the samples taken are 90 consumers.The first hypotesis finding shows the promosi influences significantly on the Consumer Buy Interest of PT Green Deli Holidays Medan. The second hypotesis shows that Trust influences significantly on the Consumer Buy Interest of PT Green Deli Holidays Medan. The third hypotesis shows that the Promosi and Trust simultaneously influence significantly on the Consumer Buy Interest of PT Green Deli Holidays Medan. In partial, the Trust variable shows more dominantly than the Promotion of PT Green Deli Holidays Medan. This means that the Consumer Buy Interest of PT Green Deli Holidays Medan are influenced highly by the Trust and it is the Trust that gives mostly.